Solid electrolyte film, preparation method thereof and lithium-oxygen battery

By using the separator matrix in the lithium oxygen battery to soak and dry and cure it in the electrolyte slurry, a solid electrolyte film with high mechanical properties and high energy density is formed, which solves the safety hazards and performance degradation of liquid electrolytes and improves lithium oxygen Cycling performance and safety of the battery.

CN119315098APending Publication Date: 2025-01-14NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411414351.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The commonly used liquid electrolytes in traditional lithium oxygen batteries have safety hazards and degradation of performance, and the ionic conductivity of the solid electrolyte film is not high, which limits the circulation performance and charge and discharge capacity of the lithium oxygen battery.

Method used

Solid electrolyte film is prepared by soaking and drying the separator matrix in the electrolyte slurry, and copolymerizing and curing it with rigid chain polymer, flexible chain polymer and lithium salt to form an electrolyte layer with high mechanical properties and high energy density, thereby improving the battery Safety and structural stability.

Benefits of technology

It effectively improves the circulation performance and energy density of lithium oxygen batteries, while enhancing the safety and mechanical properties of the batteries, reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315098A_ABST
    Figure CN119315098A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte film, a preparation method thereof and a lithium-oxygen battery, and belongs to the technical field of solid-state batteries. The preparation method provided by the invention comprises the following steps: infiltrating a diaphragm substrate in electrolyte slurry, and then drying and curing to obtain a solid electrolyte film; the electrolyte slurry comprises the following components in parts by mass: 4-14 parts of rigid chain polymer, 1-8 parts of flexible chain polymer, 1-8 parts of lithium salt and 35-200 parts of organic solvent. According to the invention, the diaphragm matrix is infiltrated in the electrolyte slurry, so that the rigid chain polymer, the flexible chain polymer and the lithium salt enter the diaphragm matrix, and an electrolyte layer can be formed on the diaphragm matrix after curing, so that the mechanical property of the solid electrolyte diaphragm can be effectively improved; and meanwhile, the diaphragm matrix serving as a base material has a good gas insulation effect and serves as a carrier of the electrolyte layer, so that the safety can be effectively improved while high energy density is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte film and a preparation method thereof, and a lithium-oxygen battery. Background Art

[0002] With the continuous growth of energy demand and the increasing attention to environmental protection, the development of high-performance, safe and reliable energy storage equipment has become an important direction of scientific research today. Lithium-oxygen batteries, as a new type of energy storage system with high theoretical energy density, use lithium and oxygen as active substances in the positive electrode and lithium metal in the negative electrode. The theoretical energy density can reach several times that of traditional lithium-ion batteries, and it has the advantages of being environmentally friendly and non-toxic, which has attracted widespread attention from researchers and practitioners.

[0003] However, there are many problems with the liquid electrolytes commonly used in traditional lithium-oxygen batteries. Once the liquid electrolyte leaks, it is easy to cause safety accidents such as short circuit, combustion or even explosion, posing a major safety hazard. At the same time, the operating temperature range of the liquid electrolyte is narrow, and its performance will drop sharply at high or low temperatures. In addition, the liquid electrolyte is also prone to side reactions with the electrode materials, thereby reducing the capacity and service life of the lithium-oxygen battery.

[0004] Therefore, solid electrolyte films are often used instead of liquid electrolytes in lithium-oxygen batteries. By using solid films with better interface stability, side reactions with electrodes can be effectively suppressed, while improving the overall mechanical properties and structural stability of lithium-oxygen batteries. However, the ionic conductivity of commonly used solid electrolyte films is not high, which greatly limits the cycle performance and charge and discharge capacity of lithium-oxygen batteries. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a solid electrolyte film and a preparation method thereof and a lithium oxygen battery.

[0006] In a first aspect, the present invention provides a method for preparing a solid electrolyte film, comprising: infiltrating a diaphragm substrate into an electrolyte slurry and then drying and curing the diaphragm substrate to obtain a solid electrolyte film; the electrolyte slurry comprises 4-14 parts of a rigid chain polymer, 1-8 parts of a flexible chain polymer, 1-8 parts of a lithium salt and 35-200 parts of

[0007] Organic solvents.

[0008] The preparation method provided by the present invention can effectively improve the mechanical properties of the solid electrolyte diaphragm by infiltrating the diaphragm matrix into the electrolyte slurry, so that the rigid chain polymer, the flexible chain polymer and the lithium salt enter the diaphragm matrix, and after curing, an electrolyte layer can be formed in the diaphragm matrix, and the diaphragm matrix has a good gas barrier effect as a basic material, and as a carrier of the electrolyte layer, it can effectively improve safety while obtaining high energy density.

[0009] Optionally, the rigid chain polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, succinonitrile, polyethylene oxide, polyacrylonitrile, polymethacrylate, polymethylethylene carbonate and hexamethylene diisocyanate.

[0010] Optionally, the flexible chain polymer includes at least one of polyvinyl acetate, polyvinyl acetate, polyethylene glycol, tetraethylene glycol dimethyl ether, vinyl ethylene carbonate and trimethyloxysilane.

[0011] Optionally, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.

[0012] Optionally, the organic solvent includes one of N-methylpyrrolidone and N,N-dimethylformamide.

[0013] Optionally, the separator substrate is immersed in the electrolyte slurry for 1-100 min.

[0014] Optionally, after the separator substrate is soaked in the electrolyte slurry, it is dried at 30-100° C. for 5-48 hours and then cured.

[0015] In a second aspect, the present invention also provides a solid electrolyte film prepared by any of the above-mentioned preparation methods, comprising a diaphragm substrate and an electrolyte layer impregnated and solidified on the surface of the diaphragm substrate, wherein the electrolyte layer is copolymerized and solidified by a rigid chain polymer, a flexible chain polymer and a lithium salt.

[0016] In a third aspect, the present invention further provides a lithium oxygen battery, comprising a positive electrode, a negative electrode and a solid electrolyte film.

[0017] Optionally, the positive electrode comprises a porous carbon material.

[0018] Optionally, the negative electrode comprises a lithium sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The cycle specific capacity performance curve of the lithium oxygen battery prepared in Application Example 1 of the present invention;

[0020] Figure 2 The cycle specific capacity performance curve of the lithium oxygen battery prepared in Application Example 2 of the present invention;

[0021] Figure 3 The cycle specific capacity performance curve of the lithium oxygen battery prepared in Application Example 3 of the present invention;

[0022] Figure 4 The discharge curve diagram of the lithium oxygen battery prepared in Application Example 1 of the present invention;

[0023] Figure 5 The discharge curve diagram of the lithium oxygen battery prepared in Application Example 2 of the present invention;

[0024] Figure 6 This is a discharge curve diagram of the lithium oxygen battery prepared in Application Example 3 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0026] The present invention provides a method for preparing a solid electrolyte film, comprising: infiltrating a diaphragm substrate in an electrolyte slurry and then drying and curing the diaphragm substrate to obtain a solid electrolyte film. In fact, by infiltrating the diaphragm substrate in the electrolyte slurry, the electrolyte slurry can be infiltrated into the diaphragm substrate and cured on the surface of the diaphragm substrate to form a dense and uniform electrolyte layer, which can improve the mechanical properties and safety of the solid electrolyte diaphragm while improving the energy density.

[0027] Specifically, the electrolyte slurry includes 4-14 parts of rigid chain polymer, 1-8 parts of flexible chain polymer, 1-8 parts of lithium salt and 35-200 parts of organic solvent by weight. In fact, the rigid chain polymer and the flexible chain polymer penetrate into the separator matrix, crosslink and solidify on the surface thereof, and anchor the lithium salt, while the organic solvent can give the rigid chain polymer, the flexible chain polymer and the lithium salt fluidity, which helps to enter the separator matrix.

[0028] In some embodiments, the rigid chain polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, succinonitrile, polyethylene oxide, polyacrylonitrile, polymethacrylate, polymethyl ethylene carbonate and hexamethylene diisocyanate; the soft chain polymer includes at least one of polyvinyl acetate, polyvinyl acetate, polyethylene glycol, tetraethylene glycol dimethyl ether, vinyl ethylene carbonate and trimethyloxysilane; the lithium salt includes at least one of lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide and lithium hexafluorophosphate; the organic solvent includes one of N-methylpyrrolidone and N,N-dimethylformamide.

[0029] In fact, when both the rigid chain polymer and the soft chain polymer are mixed with multiple polymers, they can be mixed in any mass ratio. Similarly, when the lithium salt is compounded with multiple lithium compounds, any ratio can be used, and preferably the lithium salt can be lithium bistrifluoromethanesulfonyl imide and / or lithium bisfluorosulfonyl imide. In fact, the organic solvent preferably includes N-methylpyrrolidone and / or N-dimethylformamide, more preferably N-methylpyrrolidone.

[0030] In some embodiments, the membrane substrate is a glass fiber membrane, and the thickness of the membrane substrate is 200-1000 μm, preferably 400-800 μm, and more preferably 675 μm. In fact, by using the glass fiber membrane as a skeleton structure, the thickness of the solid electrolyte membrane can be increased, and it has good gas barrier properties.

[0031] In some embodiments, the diaphragm matrix is ​​soaked in the electrolyte slurry for 1-100 minutes, preferably for 5-60 minutes, and more preferably for 10-15 minutes, which is conducive to uniform soaking of the electrolyte slurry in the diaphragm matrix.

[0032] In some embodiments, after the diaphragm substrate is soaked in the electrolyte slurry, it is dried at 30-100°C for 5-48 hours and then solidified. Preferably, the drying temperature is 50-70°C, more preferably, the drying temperature is 60°C, and the drying time is preferably 10-14 hours, more preferably, the drying time is 12 hours.

[0033] The present invention also provides a solid electrolyte membrane prepared by any of the above optional preparation methods, comprising a membrane substrate and an electrolyte layer infiltrated and solidified on the surface of the membrane substrate, wherein the electrolyte layer is copolymerized and solidified by a rigid chain polymer, a flexible chain polymer and a lithium salt.

[0034] The present invention also provides a lithium oxygen battery, comprising a positive electrode, a negative electrode and the solid electrolyte membrane in any of the above embodiments. By applying the solid electrolyte membrane prepared by the present invention, the lithium oxygen battery can obtain extremely high energy density and greatly improve safety. At the same time, the preparation cost is low and it is easy to commercialize.

[0035] In some embodiments, the positive electrode in the lithium oxygen battery includes a porous carbon material, and the negative electrode includes a lithium sheet.

[0036] Example 1

[0037] This embodiment 1 provides a method for preparing a solid electrolyte membrane, comprising: dissolving 0.7 g of polyvinylidene fluoride, 0.3 g of polyvinyl acetate and 0.34 g of lithium bis(trifluoromethanesulfonyl)imide in 9 ml of N-methylpyrrolidone to prepare an electrolyte slurry; soaking a glass fiber membrane with a thickness of 675 μm in the electrolyte slurry for 10 minutes, taking it out and transferring it to a 60°C drying oven for drying for 12 hours to obtain a solid electrolyte membrane.

[0038] Example 2

[0039] This embodiment 2 provides a method for preparing a solid electrolyte membrane, comprising: dissolving 0.7 g of polyvinylidene fluoride, 0.3 g of polyvinyl acetate and 0.34 g of lithium bis(trifluoromethanesulfonyl)imide in 18 ml of N-methylpyrrolidone to prepare an electrolyte slurry; soaking a glass fiber membrane with a thickness of 675 μm in the electrolyte slurry for 10 minutes, taking it out and transferring it to a 60°C drying oven for drying for 12 hours to obtain a solid electrolyte membrane.

[0040] Comparative Example 1

[0041] This comparative example 1 provides a method for preparing a solid electrolyte membrane, comprising: dissolving 0.7 g of polyvinylidene fluoride, 0.3 g of polyvinyl acetate and 0.34 g of lithium bis(trifluoromethanesulfonyl)imide in 36 ml of N-methylpyrrolidone to prepare an electrolyte slurry; soaking a glass fiber membrane with a thickness of 675 μm in the electrolyte slurry for 20 minutes, taking it out and transferring it to a 60°C drying oven for drying for 24 hours to obtain a solid electrolyte membrane.

[0042] Application Example 1

[0043] This application example 1 provides a method for preparing a lithium oxygen battery, comprising: mixing 50wt.% Pt / C material, conductive carbon and polyvinylidene fluoride in a mass ratio of 8:1:1 in 8mL of N-methylpyrrolidone to prepare a conductive slurry, coating the conductive slurry on the surface of dry and clean HCP120 carbon paper and drying and curing it in a vacuum drying oven to prepare a Pt / C-based oxygen electrode; packaging a lithium sheet, the solid electrolyte membrane prepared in Example 1 and the Pt / C-based oxygen electrode to prepare a button-type lithium oxygen battery.

[0044] Application Example 2

[0045] This application example 2 provides a method for preparing a lithium oxygen battery, comprising: mixing 50wt.% Pt / C material, conductive carbon and polyvinylidene fluoride in a mass ratio of 8:1:1 in 8mL of N-methylpyrrolidone to prepare a conductive slurry, coating the conductive slurry on the surface of dry and clean HCP120 carbon paper and drying and curing it in a vacuum drying oven to prepare a Pt / C-based oxygen electrode; packaging a lithium sheet, the solid electrolyte membrane prepared in Example 2 and the Pt / C-based oxygen electrode to prepare a button-type lithium oxygen battery.

[0046] Application Example 3

[0047] This application example 3 provides a method for preparing a lithium oxygen battery, comprising: mixing 50wt.% Pt / C material, conductive carbon and polyvinylidene fluoride in a mass ratio of 8:1:1 in 8mL of N-methylpyrrolidone to prepare a conductive slurry, coating the conductive slurry on the surface of dry and clean HCP120 carbon paper and drying and curing it in a vacuum drying oven to prepare a Pt / C-based oxygen electrode; packaging the lithium sheet, the solid electrolyte membrane prepared in comparative example 1 and the Pt / C-based oxygen electrode to prepare a button-type lithium oxygen battery.

[0048] Performance Testing

[0049] The lithium oxygen batteries prepared in Application Examples 1 to 3 were heated at 0.04 mA / cm 2 The charge and discharge performance test was carried out under the current density, and the cycle specific capacity performance curves of application examples 1 to 3 are as follows: Figures 1 to 3 As shown, the discharge curves of application examples 1 to 3 are respectively as shown in Figures 4 to 6 As shown. Figures 1 to 6 It can be seen that the lithium oxygen battery prepared by the present invention has good cycle performance and capacity.

[0050] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a solid electrolyte film, characterized in that: include: The diaphragm matrix is ​​soaked in electrolyte slurry and then dried and solidified to obtain a solid electrolyte film; the electrolyte slurry comprises 4-14 parts of rigid chain polymer, 1-8 parts of flexible chain polymer, 1-8 parts of lithium salt and 35-200 parts of organic solvent in parts by mass.

2. The preparation method according to claim 1, characterized in that: The rigid chain polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, succinonitrile, polyethylene oxide, polyacrylonitrile, polymethacrylate, polymethylethylene carbonate and hexamethylene diisocyanate.

3. The preparation method according to claim 1, characterized in that: The flexible chain polymer includes at least one of polyvinyl acetate, polyvinyl acetate, polyethylene glycol, tetraethylene glycol dimethyl ether, vinyl ethylene carbonate and trimethyloxysilane.

4. The preparation method according to claim 1, characterized in that: The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.

5. The preparation method according to claim 1, characterized in that: The organic solvent includes one of N-methylpyrrolidone and N,N-dimethylformamide.

6. The preparation method according to claim 1, characterized in that: The separator substrate is immersed in the electrolyte slurry for 1-100 minutes.

7. The preparation method according to claim 1, characterized in that: After the diaphragm substrate is soaked in the electrolyte slurry, it is dried at 30-100°C for 5-48 hours and then solidified.

8. A solid electrolyte film prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises a diaphragm matrix and an electrolyte layer which is infiltrated and solidified on the surface of the diaphragm matrix, wherein the electrolyte layer is solidified by copolymerization of a rigid chain polymer, a flexible chain polymer and a lithium salt.

9. A lithium oxygen battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a solid electrolyte film prepared by the preparation method according to any one of claims 1 to 7 or a solid electrolyte film according to claim 8.

10. The lithium oxygen battery according to claim 9, characterized in that: The positive electrode comprises a porous carbon material; and / or the negative electrode comprises a lithium sheet.